Enseignants autistes : l’aboutissement d’un parcours inclusif ? - Julie Dumonteil (Éducation et Socialisation)
Based on the theoretical grounding of biographical research and its own methodological approach, this article aims to study the process of subjectivation in which autistic teachers are engaged at the start of their careers. The proposed approach will make it possible to analyze the construction through the narrative of the path of these autistic teachers within the educational institution. The objective of this study is, while not obscuring the many difficulties related, to highlight, through the words of the people concerned, their unique path and the trajectory that they define as their own. Does teaching while being autistic then represent the culmination of a path or the starting point of a truly inclusive dynamic?